(untitled) (Modern American Journal of Medical and Health Sciences, 2025)
In this work, a study was conducted on the effectiveness of a local hemostatic agent based on chitosan in modeling blood loss in laboratory animals. Four groups were compared: the intact group, the control group (without treatment), the comparison group (standard treatment), and the chitosan group. A statistical analysis of blood loss volume, bleeding stop time, and blood loss index (ml/kg) was performed. The results showed a significant decrease in these indicators in the correction groups, especially when using chitosan.